PENGARUH BUDAYA ORGANISASI, KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAAN KERJA KARYAWAN UNIVERSITAS AHMAD DAHLAN YOGYAKARTA - Sari, Tunjung Santika; Bidayati, Utik (Jurnal Fokus Manajemen Bisnis, 2018)
This study aims to determine the effect of organizational culture, communication and work environment on job satisfaction of Ahmad Dahlan University employees. In this study the population used was faculty administration employees who have an accreditation study program totaling 65 people. The sample used was 65 respondents using the saturated sampling method. The analysis technique used is multiple regression analysis. Hypothesis testing using t test shows that organizational culture has no effect on employee job satisfaction while communication and work environment influence on job satisfaction. Then through the F test shows that organizational culture, communication and work environment simultaneously affect job satisfaction.